Solitary, well-circumscribed, depressed palmar lesion - Toberer, Ferdinand; Werchau, Siegfried Arthur; Hantschke, Markus; Hassel, Jessica C.; Enk, Alexander; Hadaschik, Eva (The American journal of dermatopathology, 2015)
An abstract is unavailable.
Gesehen am 02.07.2020